2012
DOI: 10.1186/1476-511x-11-158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of babassu nut oil on ischemia/reperfusion-induced leukocyte adhesion and macromolecular leakage in the microcirculation: Observation in the hamster cheek pouch

Abstract: BackgroundThe babassu palm tree is native to Brazil and is most densely distributed in the Cocais region of the state of Maranhão, in northeastern Brazil. In addition to the industrial use of refined babassu oil, the milk, the unrefined oil and the nuts in natura are used by families from several communities of African descendants as one of the principal sources of food energy. The objective of this study was to evaluate the effects of babassu oil on microvascular permeability and leukocyte-endothelial interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
2
11
0
7
Order By: Relevance
“…The results suggested that unrefined babassu oil reduced microvascular leakage and protected against histamine-induced effects in postcapillary venules. 9 Excess weight and dyslipidemia are well-established risk factors for developing cardiovascular disease (CVD). 10,11 Coronary artery disease (CAD) is associated with increased serum concentrations of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) as well as reduced serum high-density lipoprotein cholesterol (HDL-c) concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that unrefined babassu oil reduced microvascular leakage and protected against histamine-induced effects in postcapillary venules. 9 Excess weight and dyslipidemia are well-established risk factors for developing cardiovascular disease (CVD). 10,11 Coronary artery disease (CAD) is associated with increased serum concentrations of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) as well as reduced serum high-density lipoprotein cholesterol (HDL-c) concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Babassu is the generic name given to the oil palm trees belonging to the Palmae family that are members of the genera Orbignya and Attalea. The Babassu palm is native from Brazil and its oil is the extractive product produced most in Brazil, contributing significantly to the economy of some Brazilian states (5). The importance of Babassu oil for cosmetics is related to its composition.It presents emollient properties and can promote skin hydration without increasing oiliness.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of Babassu oil for cosmetics is related to its composition.It presents emollient properties and can promote skin hydration without increasing oiliness. Previous studies have shown that Babassu oil contains high quantities of triacylglycerides, such as lauric, myristic and oleic acids (5,6). Approximately 82-88% of the oil is composed by saturated fatty acids and 12-18% is made up of unsaturated acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations